Błąd co do przymiotu osoby u powoda (kan. 1097 § 2 KPK) i wykluczenie dobra potomstwa przez pozwaną (kan. 1101 § 2 KPK) w wyroku Roty Rzymskiej c. Monier z 13 maja 2011 r. - Góralski, Wojciech (Ius Matrimoniale, 2016)
This case concerns marriage contracted by 43-year-old D. with 34-year-old P. (after more than four-year acquaintance), which lasted for 2 years and then broke down due to notorious avoidance of the procreation by the respondent (contraception), while the petitioner when entering this marriage intended – directly and principally – woman’s effective ability to procreate. The sentence (pro nullitate) was given in third instance on two grounds of nullity: error by the petitioner concerning a quality of a person – can. 1097 § 2 CIC (for the second time) and exclusion of bonum prolis by the respondent – can. 1101 § 2 CIC (for the first time). It contains a number of noteworthy issues – both in substantial and evidential aspect; this applies both to the first and the second ground of nullity. The sentence c. Montier is a confirmation of the jurisprudence directions in the interpretation and application of both can. 1097 §3 and can. 1101 § 2 CIC – in regards to bonum prolis.